2013
DOI: 10.1038/ejhg.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clan structure on the genetic variation in a single Ghanaian village

Abstract: Socioeconomic and cultural factors are thought to have an important role in influencing human population genetic structure. To explain such population structure differences, most studies analyse genetic differences among widely dispersed human populations. In contrast, we have studied the genetic structure of an ethnic group occupying a single village in north-eastern Ghana. We found a markedly skewed male population substructure because of an almost complete lack of male gene flow among Bimoba clans in this v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Support for a correlation between genetics and claimed ancestry was also provided for the origin of the Cameroonian Nso' dynasty, whose Y chromosome haplogroup composition was shown to be compatible with one of the oral histories about its foundation (Veeramah et al, 2008). More recently, a correlation between Y chromosome variation and clan affiliation within a single village in Ghana has been observed (Sanchez-Faddeev et al, 2013).…”
Section: Addressed This Question In Patrilinealmentioning
confidence: 89%
“…Support for a correlation between genetics and claimed ancestry was also provided for the origin of the Cameroonian Nso' dynasty, whose Y chromosome haplogroup composition was shown to be compatible with one of the oral histories about its foundation (Veeramah et al, 2008). More recently, a correlation between Y chromosome variation and clan affiliation within a single village in Ghana has been observed (Sanchez-Faddeev et al, 2013).…”
Section: Addressed This Question In Patrilinealmentioning
confidence: 89%
“…As a result of the polygynous and patrilocal culture in the research area, men preferentially marry women from outside the region. Previous analyses of this study population have confirmed that the female-mediated gene flow is nearly fully random and prevents population stratification of autosomal genes [31]. To account for possible population stratification in this study, we rigidly excluded individuals that had a different allele at less than 10% of the loci indicated by an IBS1 below 10% and SNPs that were not in Hardy-Weinberg equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the polygynous and patrilocal culture in the research area, the female-mediated gene flow is nearly fully random [31]. Multidimensional scaling (MDS) analysis did not reveal any population stratification.…”
Section: Methodsmentioning
confidence: 99%
“…All SNPs were in Hardy–Weinberg equilibrium, with one exception where a minor deviation was observed (Kuningas et al ., 2009). We have recently reported that population stratification is unlikely to influence associations with genetic variation in autosomal genes, as analysis of autosomal DNA, mtDNA and y-chromosomal genetic variation patterns in the research area revealed that female-mediated gene flow is nearly fully random, whereas male-mediated gene flow is highly reduced (Sanchez-Faddeev et al ., 2013). This genetic substructure is an immediate result of the patrilocal society.…”
Section: Methodsmentioning
confidence: 99%